Manhaj at-Tarjih Inda Asy-Syeikh Muhammad Sholih Al-Utsaimin fi Masail az-Zakati wa al-Waqfi min Khilali Kitabihi as-Syarhul al-Mumti' - SUFITRA, IPAN, Dr. M. Muindinillah Basri, M.A, Dr. Moh. Abdul Kholiq Hasan, M.A, M. Ed (2017)
One of the good book as reference in fiqh complication today is the book entitle Asy-Syarhu Al-Mumti' created by Syeikh Muhammad Sholih Al-Utsaimin. This book is to explain the matan Zaad Al-Mustaqni', a small book describing many accurate argument from Hambali's view. Although, the book named Asy-Syarhul Mumti' describes the views of Islam in Hambali's ones, nut in its book selected mostly the arguments contrasting the Hambali's view. This is the unique and the extraordinary book. Even, that book is argued that the book is not only to explain (syarah) something, but olso the book -its self-is discuss in broad explanation and the great discussion..To begin with, this thesis is to analyze that book from many arguments being considerate and what method being conducted in correcting those arguments. The book named Asy-Syarhu Al-Mumti' is the big book and having the broad explanations so that this thesis to focus on fiqh views especially about zakat and wakaf. From the last research the writer found, there are thirteen complications concerning zakat and ten complications concerning wakaf being corrected. From the fourty complications being corrected, there are twenty six corrections which dispute with Hambali view. The others are suitable with Hambali's view constituting the view of the book writer..In considering the arguments, Syeikh Muhamaad Sholih Al-Utsaimin used some consideration methods;1) considering by dalil (proposition ) clearly; 2) considering by explaining the comparison of verdict statue; 3) considering by reviewing back from the original verdict; 4) considering by viewing what the khulafaur rosyidin do; 5)considering by viewing the verdict reasons and the meaning of hadits; 6) considering by viewing the words and its discoverer of the hadist; 7) considering by analyzing (ta'til); 8) considering by bringing out the hadist in the same way (truly mean); 9) considering by viewing the useful and unuseful (of that arguments); 10) considering by submitting the two arguments which are contradictions..For the other researches who focus on fiqh in his/her research, the ulama's book like the book the writer found (entiltled Asy-Syarhul Mumti'), it is so necessary to know that, that book describing much about fiqh that improve the researcher and the learner's Islamic knowledge. So that the complications of fiqh which are come in this term of zakat and wakaf could be answered by right ways and appropriate arguments. The writer hopes that learners who read this research will get directions after learn and learn this if only chapter by chapter the learners read or partly.